The TPACK Profile of Chemistry Prospective Teachers in Microteaching Class, University of Bengkulu - Febrian Solikhin; Salastri Rohiat (Universitas Pendidikan Ganesha, 2023)
The low knowledge of TPACK among senior semester students is the main reason for conducting this research. Whereas this knowledge supports them to become a teacher. When the profile is known, the researcher as well as the study program lecturer can prepare and improve the student’s TPACK. This research is descriptive research with a quantitative approach. The purpose of this study was to analyze the TPACK profile of prospective chemistry teacher in the microteaching class. The research subjects were students of the chemistry education study program, University of Bengkulu who took the course. The instrument used is the TPACK questionnaire. This TPACK questionnaire consists of aspects of TK, PK, CK, TPK, TCK, PCK, and TPACK. This questionnaire uses a Likert scale. The results of the study were then categorized into 5 categories in each aspect. This category is useful for grouping students. The results of this study stated that students of the chemistry education study program who took microteaching courses knew this TPACK in the good category. Almost all aspects have an average score in the good category, only 1 aspect has a sufficient average score.